QED effects in scattering processes involving atomic bound states: radiative recombination - Lindgren, Ingvar; Salomonson, Sten; Holmberg, Johan (Physical review. A, Atomic, molecular, and optical physics, 2014)
The standard perturbative expansion of the S matrix cannot generally be used in the treatment of atomic scattering processes, involving atomic bound states, due to the special type of singularity that can appear here. It is demonstrated in the present paper that as a consequence of the optical theorem for free particles the effective Hamiltonian is closely related to the total cross section, a relation that is valid also when bound states are present. This implies that methods designed for structure calculations also can be used in dynamical processes. We have found that the covariant-evolution-operator technique that we have developed for structure calculations is here particularly useful. This is a consequence of the fact that the regular part of this operator (the Green's operator), running over all times, is essentially equal to the effective Hamiltonian and therefore directly related to the scattering cross section. In this paper the procedure is demonstrated for the case of radiative recombination.
Gesehen am 12.08.2020